2005
DOI: 10.1111/j.1365-313x.2005.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Nod factors and a diffusible factor from arbuscular mycorrhizal fungi stimulate lateral root formation in Medicago truncatula via the DMI1/DMI2 signalling pathway

Abstract: SummaryLegumes form two different types of intracellular root symbioses, with fungi and bacteria, resulting in arbuscular mycorrhiza and nitrogen-fixing nodules, respectively. Rhizobial signalling molecules, called Nod factors, play a key role in establishing the rhizobium-legume association and genes have been identified in Medicago truncatula that control a Nod factor signalling pathway leading to nodulation. Three of these genes, the so-called DMI1, DMI2 and DMI3 genes, are also required for formation of my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
227
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 310 publications
(245 citation statements)
references
References 45 publications
16
227
2
Order By: Relevance
“…Consistent with this proposal, it has been shown that Nod factor and Myc factors can both induce LR development (Oláh et al, 2005;Maillet et al, 2011). Within the G1, G2, and G3 clusters, we identified 22 genes homologous to known Arabidopsis regulators of root and LR development (Table I).…”
Section: Hierarchical Clustering Highlights Nod Factor-and Et-dependesupporting
confidence: 65%
See 1 more Smart Citation
“…Consistent with this proposal, it has been shown that Nod factor and Myc factors can both induce LR development (Oláh et al, 2005;Maillet et al, 2011). Within the G1, G2, and G3 clusters, we identified 22 genes homologous to known Arabidopsis regulators of root and LR development (Table I).…”
Section: Hierarchical Clustering Highlights Nod Factor-and Et-dependesupporting
confidence: 65%
“…Nod factors stimulate the formation of LRs (Oláh et al, 2005); thus, the increased expression of LR developmental genes could simply reflect additional LR initiation. Alternatively, the genes regulating LR primordium initiation may perform analogous functions required for the initiation of nodule development.…”
Section: Hierarchical Clustering Highlights Nod Factor-and Et-dependementioning
confidence: 99%
“…Consistent with this hypothesis, it has been shown that both Nod and Myc symbiotic factors, in addition to their role in host recognition and nodule organ formation, stimulate lateral root development (Oláh et al, 2005;Maillet et al, 2011). This effect on lateral root development may represent their ancestral function, suggesting that nodule organogenesis programs have evolved by co-option of lateral root developmental programs triggered by Nod factor-like signaling molecules.…”
Section: Discussionsupporting
confidence: 50%
“…While the production of NO is evident, its role in the early response of the host plants to AM fungal signals remains unclear. One possibility is that NO is active in the signaling pathway that stimulates lateral root formation (Oláh et al 2005;Mukherjee and Ané 2011); both responses are in fact DMI1-/DMI2-dependent and DMI3-independent. This intriguing possibility, which requires further investigation, is also supported by the well-known presence of NO in root meristems and at sites of lateral root emergence (Correa-Aragunde et al 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the upregulation of a membrane steroid-binding protein was also shown to be induced in epidermal/subepidermal cells in the vicinity of AM fungal hyphae (Kuhn et al 2010). Diffusible AM fungal signals were also shown to activate early events, such as changes in cytosolic (Navazio et al 2007;Kosuta et al 2008) and nuclear Ca2+ concentration (Chabaud et al 2011), and delayed processes, such as root branching (Oláh et al 2005) and starch accumulation in the root cortex (Gutjahr et al 2009). Recently, fungal exudates from Glomus intraradices were shown to contain a mixture of sulfated and nonsulfated lipochitooligosaccharides (LCO), which are responsible for the activation of MtENOD11 gene expression and the induction of lateral roots formation (Maillet et al 2011).…”
Section: Introductionmentioning
confidence: 99%